Design, synthesis of new 2,4-thiazolidinediones: In-silico, in-vivo anti-diabetic and anti-inflammatory evaluation - Shankar Gharge; Shankar G. Alegaon; Shriram D. Ranade; N.A. Khatib; Rohini S. Kavalapure; B.R. Prashantha Kumar; Vinod D; Nandkishor B. Bavage (Elsevier, 2024)
In this study, a series of nine novel heterocyclic compounds were synthesized through a concise three-step reaction process. The synthesis involved Knoevenagel condensation at the 5th position of the 2,4-thiazolidinedione or rhodanine ring-system. Comprehensive physicochemical and spectral analyses, including FTIR, Mass, 1H NMR and 13C NMR, were performed to characterize the synthesized compounds. The synthesized derivatives were subjected to evaluation for their potential in various therapeutic domains. In-vivo anti-diabetic activity was assessed diabetes induced wistar rats, anti-inflammatory effects were gauged using the carrageenan and formalin induced rat paw edema model. Additionally, the in-vitro PPAR-γ modulatory activity, glucose uptake by using Saccharomyces cerevisiae and rat hemidiaphragm and cyclooxygenase inhibitory activity along with scavenge free radicals was tested by FRAP and DPPH method. According to the potential binding patterns of the most potent anti-diabetic compounds, namely 7a and 13a with the active sites of target PPAR-γ (PDB ID: 5U5L), was obtained through molecular docking using Schrodinger's Glide model. Among the tested compounds, the compound 13a demonstrated significant antidiabetic activity with reduction in blood glucose levels (108.5 ± 2.171 mg/dL), comparable to the effect of pioglitazone (101.66 ± 0.95 mg/dL), similarly anti-inflammatory activity at fourth hour paw volume 93.6% and thickness at 3.99 ± 0.076 mm, respectively closer to that of standard drug diclofenac sodium (91.2% and 4.7 ± 0.057 mm) in carrageenan-induced paw edema in rat. The compound 13a displayed promising COX-2 inhibitory activity (IC50 = 7.82 μM) and DPPH antioxidant activity showcasing its multifaceted therapeutic potential. This study not only presents multi-targeting approach and highlights the significant potential compounds as a lead molecule for further therapeutic development.